Efficacy of live attenuated, vector and immune complex infectious bursal disease virus (IBDV) vaccines in preventing field strain bursa colonization: A European multicentric study - Ramon, Gema; Legnardi, Matteo; Cecchinato, Mattia; Cazaban, Christophe; Tucciarone, Claudia Maria; Fiorentini, Laura; Gambi, Lorenzo; Mato, Tamas; Berto, Giacomo; Koutoulis, Kostas; Franzo, Giovanni (Frontiers in Veterinary Science, 2022)
Infectious bursal disease virus (IBDV) is among the most relevant and widespread immunosuppressive agents, which can severely damage poultry farming by causing direct losses, predisposing the host to secondary diseases and reducing the efficacy of vaccination protocols against other infections. IBDV has thus been the object of intense control activities, largely based on routine vaccination. However, the need for protecting animals from the infection in the first period of the production cycle, when the bursa susceptibility is higher, clashes with the blanketing effect of maternally derived antibodies. To overcome this issue, other strategies have been developed besides live attenuated vaccines, including vector vaccines and immune complex (icx) ones. The present study aims to investigate, in field conditions, the efficacy of these approaches in preventing IBDV infection in laying chickens vaccinated with either live attenuated, vector or icx vaccines. For this purpose, a multicentric study involving 481 farms located in 11 European countries was organized and IBDV infection diagnosis and strain characterization was performed at 6 weeks of age using a molecular approach. Vaccine strains were commonly detected in flocks vaccinated with live or icx vaccines. However, a significantly higher number of field strains (characterized as very virulent IBDVs) was detected in flocks vaccinated with vector vaccines, suggesting their lower capability of preventing bursal colonization. Different from vector vaccines, live and icx ones have a marked bursal tropism. It can thus be speculated that vaccine virus replication in these sites could limit vvIBDV replication by direct competition or because of a more effective activation of innate immunity. Although such different behaviour doesn’t necessarily affect clinical protection, further studies should be performed to evaluate if vvIBDV replication could still be associated with subclinical losses and/or for viral circulation in a “vaccinated environment” could drive viral evolution and favor the emergence of vaccine-escape variants.